2011
DOI: 10.1371/journal.pone.0024737
|View full text |Cite
|
Sign up to set email alerts
|

“Pseudo-Beijing”: Evidence for Convergent Evolution in the Direct Repeat Region of Mycobacterium tuberculosis

Abstract: Background Mycobacterium tuberculosis has a global population structure consisting of six main phylogenetic lineages associated with specific geographic regions and human populations. One particular M. tuberculosis genotype known as “Beijing” has repeatedly been associated with drug resistance and has been emerging in some parts of the world. “Beijing” strains are traditionally defined based on a characteristic spoligotyping pattern. We used three alternative genotyping techniques to revisit the phylogenetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 19 publications
3
51
0
1
Order By: Relevance
“…Convergent evolution has been described as relatively common when using the direct repeat (DR) region as a genetic marker, and incorrect classification of lineages by spoligotyping was recently evidenced in Brazil (26) and more frequently when the deletion of large blocks of spacers occurs, such as causing misclassification of M. tuberculosis of the Beijing type (46). Therefore, our observation of human isolates with the SIT863 spoligotype characteristic of PINI2, together with the lack of notification of M. pinnipedii as a cause of human TB, lead us to believe that we might be dealing with cases of misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Convergent evolution has been described as relatively common when using the direct repeat (DR) region as a genetic marker, and incorrect classification of lineages by spoligotyping was recently evidenced in Brazil (26) and more frequently when the deletion of large blocks of spacers occurs, such as causing misclassification of M. tuberculosis of the Beijing type (46). Therefore, our observation of human isolates with the SIT863 spoligotype characteristic of PINI2, together with the lack of notification of M. pinnipedii as a cause of human TB, lead us to believe that we might be dealing with cases of misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…However, spoligotyping is well known to show gene conversions, and strains having no genetic relationship sometimes show the same spoligotype (3, 26). Fenner et al (35) reported pseudo-Beijing strains that had a typical Beijing spoligotype even though they actually belonged to the CAS family. This type of confusion seems to occur especially in areas that have a higher prevalence of principal genetic group 1 (PGG1) lineages, including the EAI, CAS, and east Asian lineages, since PGG1 strains usually possess spacers 35 and 36, which are lacking in PGG2 and PGG3 strains (3,36).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular clusters were defined as a group of completely identical isolates in the spoligotyping and MIRU-VNTR pattern. We determined the main M. tuberculosis lineages by single nucleotide polymorphisms (SNPs) using multiplex real-time PCR with fluorescence-labeled probes (TaqMan; Applied Biosystems) adopted from previous studies (7,13,14,18). Region of difference (RD) deletion PCRs were performed for RD702 and RD711, which define the West African lineages (14).…”
Section: Methodsmentioning
confidence: 99%